Evaluation of methods for long term storage of the boysenberry downy mildew pathogen Peronospora sparsa - Mudiyanselage, A.M. Herath; Jaspers, M.V.; Ridgway, H.J.; Walter, M.; Langford, G.I.; Jones, E.E. (New Zealand Plant Protection, 2013)
Downy mildew of boysenberry is caused by the biotrophic pathogen Peronospora sparsa To ensure supplies of viable spore inoculum for infection experiments six storage methods were assessed the leaf discs cut from sporulating areas of the leaf stored dry or in 20 glycerol and spores were suspended in 20 glycerol all three of which were stored at either 20C or 80C After 1 2 4 or 6 months storage spore viability and the capability to infect leaf discs were evaluated Storage methods had no significant effects on spore germination or infection Storage time and temperature significantly (P